Employee Engagement Under Pressure: The Conditional Effects of Job Resources and Target Pressure on Employee Performance in the Banking Sector - Sintia Ulandari; Suhardi Suhardi; Afrizal Afrizal (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
The intensification of performance pressure in modern banking raises concerns about the sustainability of employee engagement under target-driven systems. Although employee engagement is traditionally viewed as a positive psychological mechanism enhancing performance, aggressive key performance indicators, digital monitoring, and continuous target evaluation may constrain its beneficial effects. This study examines employee engagement as a psychological mechanism linking job resources and work motivation to employee performance and investigates the moderating role of target pressure in the banking sector. Grounded in Job Demands–Resources (JD-R) Theory and Conservation of Resources (COR) Theory, the study conceptualizes engagement as a conditional mechanism whose effectiveness may diminish under excessive performance demands. A quantitative explanatory design was employed using survey data from 200 banking employees working within target-based performance systems in Indonesia. Generalized Structured Component Analysis (GSCA) was used to test direct, mediating, and moderating relationships. The findings show that job resources and work motivation positively influence employee engagement, which significantly improves employee performance. Employee engagement also mediates the effects of job resources and work motivation on performance. However, target pressure significantly weakens the positive engagement–performance relationship, indicating that engagement is context-dependent and potentially unsustainable in high-pressure environments. The study extends JD-R Theory by integrating resource depletion and strain pathway perspectives and advances an engagement-under-pressure perspective. Practically, organizations should balance performance demands with employees’ psychological resource sustainability through adaptive target management and sustainable human resource practices.